Edukasi Online tentang Pengembangan Karir dan Enterpreneur - Puput Iswandyah Raysharie (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
This community dedication in the form of career and entrepreneurship guidance webinars aims to provide guidance and advice to the community in preparing for careers and running their business. In this webinar activity, participants will be given an understanding of how to choose a career and develop the right business through presentations and discussions with experts in the field of career and entrepreneurship. In addition, the webinar activities also allow participants to expand their network with people who are experienced and have expertise in the fields of career and entrepreneurship so that they can help them build a successful career or business in the future.